'Advisers or Fellow-revisers': Recognition, Status and the Revised Version. Issue 1 (31st October 2012) - Cadwallader, Alan H.
Abstract The Revised Version is recalled in the history of English language biblical versions because of the intense public debates over its potential to supplant the Authorized Version of 1611. These highly politicized contests over text and translation have continued through to the present day and have sidetracked attention from the deeper issues of identity and status associated with scholarship and national standing. Philip Schaff led a committed and ambitious group of American Protestant and Unitarian scholars in efforts to be credited as equal participants with the English Revisers in the massive project of the revision of the long-standing and much-loved English translation. The formation of the American Revised Version Committee within a year of the commencement of the work of revision by the two English Revision Companies ushered in an immense behind-the-scenes struggle over the requisite standing for decisions over the wording of the revised translation. Linguistics and text became the arena on which contests for recognition, national pride and scholarly achievement were fought. The choice of weapons of influence ranged from promotion of academic ability to rhetorical appeals to threats of commercial subversion. This paper explores the significance of American efforts to be involved credibly and influentially in the work that culminated in the Revised Version of 1881/1885 in England and (as a testament to the standing of American biblical scholarship and the failure of international cooperation) the distinct American Standard Version of 1901.